Analisis Sistem Keamanan Wireless Local Area Network (WLAN) Menggunakan Akses Tethering: Analisis Sistem Keamanan Wireless Local Area Network (WLAN) Menggunakan Akses Tethering - Astutik Zaerani; Lalu Delsi Samsumar; Karim, Muh Nasirudin; Emi Suryadi (Yayasan Nuraini Ibrahim Mandiri, 2024)
Current technology continues to develop in various ways, network security needs to be considered along with the development of these technological facilities. Tethering is a technological facility that is widely used today, such as in residential areas, rented houses, boarding houses and campuses. The testing techniques used are sniffing and scanning using the Arp-scan and Bettercap tools. The results obtained from the test indicate that the security of the Wireless Local Area Network (WLAN) network using tethering access is not safe enough to use. This is evidenced by the results of the test in the form of data obtained from the impact of the attack in the form of Username, Password, and sites accessed by the target indicating that the security of the Wireless Local Area Network (WLAN) network in the tethering process is still categorized as unsafe and needs to be improved. Keywords: WLAN, Tethering, Pentest, Sniffing, Scanning